1989
DOI: 10.1111/j.1365-2265.1989.tb01236.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of Calcitonin Gene‐related Peptide (Cgrp) but No Evidence for CGRP Gene Expression in Non‐small Cell Lung Carcinomas

Abstract: Calcitonin gene-related peptide (CGRP) is a hormone formed by alternative post-transcriptional processing of the calcitonin gene. It is a neuropeptide localized to discrete regions of the central nervous system (CNS) and in nerve fibres associated with blood vessels. It is also expressed in medullary carcinomas of the thyroid and lung carcinoma cell lines. The latter finding suggests a possible value for CGRP as tumour marker in lung carcinomas. In this investigation of 22 patients undergoing operation for lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
1993
1993

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Previous investigations have shown that certain lung carcinoma cell-lines may express CGRP Riley et al, 1986) and Riley et al also found increased circulating CGRP-concentrations in lung carcinoma patients. In a previous paper we have demonstrated that CGRP concentrations are significantly elevated in patients with non-SCLC, but this elevation also seemed to be unrelated to synthesis by the tumours since in-situ hybridization and immunohistochemistry showed negative reactions in all the tumours investigated (Schifter et al, 1989). Expression of CGRP has also been demonstrated in other neuroendocrine tumours, including phaeochromocytomas and carcinoid tumours (Johannsen et al, 1987;Funa, 1991).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous investigations have shown that certain lung carcinoma cell-lines may express CGRP Riley et al, 1986) and Riley et al also found increased circulating CGRP-concentrations in lung carcinoma patients. In a previous paper we have demonstrated that CGRP concentrations are significantly elevated in patients with non-SCLC, but this elevation also seemed to be unrelated to synthesis by the tumours since in-situ hybridization and immunohistochemistry showed negative reactions in all the tumours investigated (Schifter et al, 1989). Expression of CGRP has also been demonstrated in other neuroendocrine tumours, including phaeochromocytomas and carcinoid tumours (Johannsen et al, 1987;Funa, 1991).…”
Section: Discussionmentioning
confidence: 88%
“…In-situ hybridization for CGRP mRNA was performed on 17 tumours. The investigation was performed as described previously (Schifter et al, 1989) using a CGRP cRNA probe derived from a fragment of the calcitonin/cc-CGRP gene, containing exon 6 of the gene. The probe is specific for a-CGRP mRNA under the washing conditions employed.…”
Section: In-situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation